2002
DOI: 10.1159/000057962
|View full text |Cite
|
Sign up to set email alerts
|

Familial Combined Pituitary Hormone Deficiency Caused by <i>PROP-1</i> Gene Mutation

Abstract: Background: Mutations of the prophet of PIT-1 (PROP-1), a paired-like homeodomain transcription factor which is responsible for early embryonic pituitary development, have recently been reported as a cause of combined pituitary hormone deficiency. Methods: We describe the phenotype, long-term auxological data and MRI findings in two families with 4 affected members, all of whom have a mutation of the PROP-1 gene. GH, TSH, PRL, LH and FSH were completely deficient in all patients. Results: ACTH deficiency was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
10
2
Order By: Relevance
“…Only two of seven adult patients required cortisol substitution in early adulthood. Therefore, the prevalence, age of onset and clinical significance of late-onset ACTH deficiency in patients with PROP1 gene defects remains a matter of controversy (17,23,26,27). From our data and published data, it may be concluded that late-onset ACTH deficiency may develop during the third or fourth decade of life in some affected individuals.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Only two of seven adult patients required cortisol substitution in early adulthood. Therefore, the prevalence, age of onset and clinical significance of late-onset ACTH deficiency in patients with PROP1 gene defects remains a matter of controversy (17,23,26,27). From our data and published data, it may be concluded that late-onset ACTH deficiency may develop during the third or fourth decade of life in some affected individuals.…”
Section: Discussionmentioning
confidence: 65%
“…In those patients not diagnosed and treated in time, growth retardation progressed, leading to a mean height SDS of 2 4.1 at 5 years of age. The question of when GH deficiency manifests in patients with PROP1 gene defects is a matter of controversy (17,26,27). This longitudinal study indicates that growth retardation starts earlier than previously suggested, calling for initiation of GH therapy at young age.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, we included Czech patients from a population-based testing for genetic causes of pituitary insufficiency in childhood and adulthood [6], as well as pediatric and adult patients from Germany [16], Poland, Lithuania, and Russia. The study cohort was also complemented by several adult patients who originated from Austria [14]. Ethical review board approval was obtained, and all applicable regulatory requirements in the participating countries were followed.…”
Section: Methodsmentioning
confidence: 99%
“…The true nature, prevalence, and natural development of pituitary masses due to PROP1 mutations have so far been studied only in limited cohorts of patients [3,4,5,13,14,15,16,17,18,19]; therefore, we aimed to establish a representative group of affected patients allowing more detailed analysis over the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothalamic-pituitary-adrenal axis of the 2 older sisters was intact. Although overt ACTH deficiency is uncommon in patients carrying PROP-1 mutations, studies have shown a tendency towards partial ACTH and cortisol deficiencies with age in some of them [4, 10, 11, 12, 13]. The hormonal insufficiency was not linked with the R120C mutation or other PROP-1 mutations, but was attributed either to the accumulation of amorphous material in the pituitary gland or to progressive apoptosis of the corticotropes due to lack of signals from other pituitary cell lineages.…”
Section: Discussionmentioning
confidence: 99%